Crystal structure of 1H-1,2,3-Triazolo[4,5-b]-pyridin-4-ium nitrate, C5H5N5O3 - Zhou Meng-Shu; Fu Hong-Ru (Zeitschrift für Kristallographie - New Crystal Structures)
C5H5N5O3, orthorhombic, Pnma (no. 62), a = 13.4643(13) Å, b = 6.2866(10) Å, c = 9.1138(9) Å, V = 771.43(16) Å3, Z = 4, Rgt(F) = 0.0517, wRref(F2) = 0.1317, T = 293 K.